Pulmonary Arterial Elastance and INTERMACS-Defined Right Heart Failure Following Left Ventricular Assist Device. (August 2019) - Muslem, Rahatullah; Ong, Chin S.; Tomashitis, Brett; Schultz, Jessica; Ramu, Bhavadharini; Craig, Michael L.; Van Bakel, Adrian B.; Gilotra, Nisha A.; Sharma, Kavita; Hsu, Steven; Whitman, Glenn J.; Leary, Peter J.; et al.
Abstract : Background: Acute right heart failure (RHF) after left ventricular assist device implantation remains a major source of morbidity and mortality, yet the definition of RHF and the preimplant variables that predict RHF remain controversial. This study evaluated the ability of (1) INTERMACS (Interagency Registry for Mechanically Assisted Circulatory Support) RHF classification to predict post-left ventricular assist device survival and (2) preoperative characteristics and hemodynamic parameters to predict severe and severe acute RHF. Methods and Results: An international, multicenter study at 4 large academic centers was conducted between 2008 and 2016. All subjects with hemodynamics measured by right heart catheterization within 30 days before left ventricular assist device implantation were included. RHF was defined using the INTERMACS definition for RHF. In total, 375 subjects were included (mean age, 57.4±13.2 years, 54% bridge-to-transplant). Mild RHF was most common (34%), followed by moderate RHF (16%), severe RHF (13%), and severe acute RHF (9%). Estimated on-device survival rates at 2 years were 72%, 71%, and 55% in the patients with none, mild-to-moderate, and severe-to-severe acute RHF, respectively ( P =0.004). In addition, the independent hazard ratio for mortality was only increased in the patients with severe-to-severe acute RHF (hazard ratio, 3.95; 95% CI, 2.16–7.23; P <0.001). INTERMACS-defined RHF was superior to postimplant inotrope duration alone in the prediction of all-cause mortality. In multivariable analysis, older age, lower INTERMACS classes, and higher pulmonary arterial elastance (ratio of systolic pulmonary artery pressure to stroke volume) before left ventricular assist device, were identified as significant predictors of severe-to-severe acute RHF. Stratifying patients by ratio of systolic pulmonary artery pressure to stroke volume and right atrial pressure significantly improved the discrimination between patients at risk for severe-to-severe acute RHF. Conclusions: The INTERMACS RHF classification correctly identifies patients at risk for mortality, though this risk is only increased in patients with severe-to-severe acute RHF. Several predictors for RHF were identified, of which ratio of systolic pulmonary artery pressure to stroke volume was the strongest hemodynamic predictor. Coupling ratio of systolic pulmonary artery pressure to stroke volume with right atrial pressure may be most helpful in identifying patients at risk for severe-to-severe acute RHF. Abstract : Supplemental Digital Content is available in the text.